Analysis of Sociocultural Factors for Schools Drop Out among Girls in Tanzania - Mgambi Msafiri; Cai Lianyu (Research Aspects in Arts and Social Studies Vol. 9, 2023)
This study investigates the sociocultural factors that contribute to high dropout rates among girls at junior secondary school in the mara region, Tanzania. Students dropping out of school is a significant concern for any government or society. A qualitative analysis was carried out to investigate the extent to which the social-cultural factors led to the high number of girls failing to complete their junior secondary studies in the Mara region by using a semi-structured interview and documentary review. With the semi-structured interview, the author interviewed fifteen parents and guardians, ten teachers (including school directors), and twenty dropout girls who participated in the study’s discussions. This increased the total number of study participants to 45. The interview subjects, both men and women, were specifically chosen to be pertinent to the present study. The study discovered that early marriage, female genital mutilation, household activities, social attitudes against educating girls, and low levels of education among parents all contribute to girls dropping out of school. It is suggested that stakeholders prioritize girls’ education in order to avoid gender disparities. The government and NGOs should educate society and ensure that education in the Mara region should be prioritized for both boys and girls. To provide girls who have been subjected to FGM with a safe place, the government should prioritize the establishment of rescue centers within districts, with the assistance of local administration and other child activists.